Indian Contitution and Transgender Persons in India; A Critical Anylasis - Kumar, Sani; Veer Singh, Uday (Journal of Neonatal Surgery, 2025)
The Indian Constitution has progressively recognized and protected the rights of transgender people. Establishing transgender rights has been much aided by fundamental constitutional clauses including Article 14 (equal before the law), Article 15 (prohibition of discrimination), Article 19 (freedom of expression), and Article 21 (right to life and personal liberty). The Transgender Persons (Protection of Rights) Act, 2019, which has drawn criticism for failing to sufficiently address issues including marriage rights and the application of anti-discrimination laws. Constitutional rights continue to be shaped by judicial rulings, including those allowing transsexual people to partake in election procedures and wed under personal laws. Emphasizing the need of inclusive policies, legislative changes, and society acceptance to ensure substantive equality for transgender people, this abstract explores the growing constitutional jurisprudence of transgender rights in India. Individuals within the transgender community are denied fundamental human rights that every person is entitled to. While individuals from the other two genders are advancing in space exploration, robotics, and several professional domains, transgender individuals continue to seek equitable treatment within society However, the harsh reality is that transgender individuals are often prohibited from marrying their loved ones, and if they do marry, they frequently become victims of assault and discrimination. This article will examine and evaluate the legal frameworks regarding transgender individuals employed by various governments worldwide. This will address societal injustices faced by the transgender population, constitutional provisions, legislation enacted by the Government of India to support transgender individuals, and certain international laws.